Haptic-Enabled Robotic Arms to Achieve Handshakes in the Metaverse - Mohd Faisal (Université d'Ottawa / University of Ottawa, 2022)
Humans are social by nature, and the physical distancing due to COVID has converted many of our daily interactions into virtual ones. Among the negative consequences of this, we find the lack of an element that is essential to humans' well-being, which is the physical touch. With more interactions shifting towards the digital world of the metaverse, we want to provide individuals with the means to include the physical touch in their interactions. We explore the Digital Twin technology's prospect to support in reducing the impact of this on humans. We provide a definition of the concept of Robo Twin and explain its role in mediating human interactions. Besides, we survey research works related to Digital Twin's physical representation with a focus on under-actuated Digital Twin's robotic arms. In this thesis, we first provide findings from the literature, to support researchers' decisions in the adoption and use of designs and implementations of Digital Twin's robotic arms, and to inform future research on current challenges and gaps in existing research works. Subsequently, we design and implement two right-handed under-actuated Digital Twin's robotic arms to mediate the physical interaction between two individuals by allowing them to perform a handshake while they are physically distanced. This experiment served as a proof of concept for our proposed idea of Robo Twin. The findings are very promising as our evaluation shows that the participants are highly interested in using our system to make a handshake with their loved ones when they are physically separated. With this Robo Twin Arm system, we also find a correlation between the handshake characteristics and gender and/or personality traits of the participants from the quantitative handshake data collected during the experiment. Moreover, it is a step towards the design and development of Digital Twin's under-actuated robotic arms and ways to enhance the overall user experience with such a system.
Keywords: Digital Twin; Robo Twin; Under-Actuated Design; Anthropomorphic Robotic Hand, and Sensor Technology.; Human-Robot Interaction; Handshaking; Personality Characteristics